20. YÜZYILDA DİYARBAKIR İLÇELERİ TARİHİ VE İNANÇ COĞRAFYASI - ŞAHİN, NAFİZ (Fırat Üniveristesi, 1997)
Our thesis, whouse subject is in 20 th century. Diyarbakır and its towns and their historical and geographical of belief four parts. Introduction; the first, the second, and the third part. In the indroduction part: The General history of Diyarbakır is reseorched. The origin of DiyarVahr's na~? was krrv.~* as "ArrrHa" which has the meaning of "Hope" in the language of Süryani. It tbced witih Islamic Armies under the culing of Halid bin Velid in 639. H Was seized in 1085 by the sen of the Commanders of Mclikşah state: After being ruled by Artuklular, Anatolia Seljuks and Akkoyunlular all of whom are former Turkish states, the city began to beruled by ottoman Empire in 1515. In flic first part: Information is presented about thirteen historical, geographical and other important aspects, in addition to these the identical information of the villages and tons ware investigated and it was showon in charts. In the second part: The information about treligious belief of geogroph in Diyarbakır in 1 800 s has been transferred as being transloted from French to Turkish from the book Called Turquia by Vitali Cuinet. In the third and last part: The minaritics in Diyarbakır and ist towns, their pastand present sitvatians and their current religious belief of geogropy is analyzed. Under this title: The information about Christians when they came and spreaded in Diyarbakır, their situation before Islam and their worshipping places are in a detailed way given. Just after these the numbers of Christians in the environment are stated. And then Armenians, People of Süryani, Keldanil, Yezidi and other minority groups are searched in arder and with great care one by one. Besides Minorities, the stiuation of Muslims of Diyarbakır is investigated; their population, the stiuation of Alevi people and Sunni people other branches of Islam in the towons arc searched in detailed one bv one.
History and belief geography of Diyarbakır in the 20 th.
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Din; Religion; Sosyoloji; Sociology